Efficient Electrochemical Energy Conversion and Storage Performance of Combined Rare-Earth Metal Oxide-Mos2 Nanocomposite - Radhalayam, D (ELSEVIER SCIENCE SA, 2026)
For the advancement of sustainable energy technologies, high-performance electrocatalysts or electrodes are essential, and the deliberate addition of rare earth elements to transition metal dichalcogenide-based catalysts shows significant potential in improving their electrochemical properties. In the present work, the phase mixed (1T/2H) MoS2 and rare earth metal oxide (Nd2O3) based MoS2 nanocomposite are synthesized via hydrothermal route. Structural, phase, morphological, and elemental studies are showing significant changes and successful composite formation by the incorporation of Nd2O3 into MoS2. Then the composite shows the prominent HER activity in 0.5 M H2SO4, delivering 200 mV overpotential at 10 mA cm-2. Further, the same electrode exhibits superior symmetric supercapacitor performance with a specific capacitance (Csp) of 516.3 Fg-1 and energy density (E) of 71.7 Wh kg-1 in 1 M Na2SO4 electrolyte. Thus, our work paves the way for the multipurpose applications of MoS2 composites based on Nd2O3 in electrochemical energy conversion and storage technologies.